2020
DOI: 10.5565/rev/qpsicologia.1566
|View full text |Cite
|
Sign up to set email alerts
|

Historicising Cultural Sport Psychology: Dare we De-centre Methodological Eurocentrism?

Abstract: In this essay we critically reflect on our respective journeys to and within cultural sport psychology (CSP). Since the inception, CSP scholars have advocated for opening the privileged academic space for marginalised voices and omitted subject themes; as well as cautioned researchers that the CSP project itself needs to be constantly revisited and reworked to keep it in progressive flux. We argue that, despite some notable advances, CSP remains a predominantly white Anglo-American intellec-tual space and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…For example, McCarver et al (2019) found that over 80% of CMPCs identify as white, heterosexual, and able-bodied. Likewise, the results in the current study suggest that SEP was founded upon, and continuously operates from, a Eurocentric and white worldview, which perpetuates the exclusion and harm of traditionally marginalized populations and raises serious doubts that knowledge presented at AASP is relevant and generalizable to all (Ryba & Schinke, 2009;Ryba et al, 2013;Ryba et al, 2020).…”
Section: Cultural Diversity Content In Presentation Abstractsmentioning
confidence: 65%
See 1 more Smart Citation
“…For example, McCarver et al (2019) found that over 80% of CMPCs identify as white, heterosexual, and able-bodied. Likewise, the results in the current study suggest that SEP was founded upon, and continuously operates from, a Eurocentric and white worldview, which perpetuates the exclusion and harm of traditionally marginalized populations and raises serious doubts that knowledge presented at AASP is relevant and generalizable to all (Ryba & Schinke, 2009;Ryba et al, 2013;Ryba et al, 2020).…”
Section: Cultural Diversity Content In Presentation Abstractsmentioning
confidence: 65%
“…These factors notwithstanding, this finding suggests there is limited global participation at AASP conferences; thus, AASP may not be producing work that is globally relevant. Although our data do not reveal the actual nationalities of participating authors, the lack of representation, especially of those affiliated with the Global South, is concerning as this can make challenging ethnocentric viewpoints difficult (Ryba & Schinke, 2009;Ryba et al, 2020). If we are only researching and presenting on Western populations, the knowledge generated and presented at AASP is likely very limited and culturally irrelevant for most of the world.…”
Section: First Author's Country Of Affiliationmentioning
confidence: 78%
“…Melihat kebutuhan masyarakat akan aktifitas olahraga dapat menciptakan beberapa lapangan pekerjaan dibidang olahraga (Ryba et al, 2020). Untuk pembinaan olahraga, pencapaian prestasi akan membutuhkan beberapa peran pelatih, klub olahraga, sekolah olahraga, dokter olahraga, masseur, dan fisioterapis (Dias & Monteiro, 2020).…”
Section: Pendahuluanunclassified